Branchial Cleft-Like Cysts Involving 3 Different Organs: Thyroid Gland, Thymus, and Parotid Gland. Issue 42 (October 2015) - Nakazawa, Tadao; Kondo, Tetsuo; Oishi, Naoki; Tahara, Ippei; Kasai, Kazunari; Inoue, Tomohiro; Mochizuki, Kunio; Katoh, Ryohei
Abstract : Abstract: Branchial cleft cysts (BCCs) are also named lateral cervical cysts and widely acknowledged as being derived from embryonic remnants. Lymphoepithelial cysts (LECs) generally show microscopic features that are identical to those of BCCs, and rarely occur at unusual sites or organs. A case of multiple cysts arising in both lobes of the thyroid gland, thymus, and right parotid gland in a 41-year-old man is reported. Clinically, the patient presented with Hashimoto's thyroiditis for about 20 years and had past histories of idiopathic thrombocytopenic purpura and severe respiratory infection. This case is unusual in that multiple cysts arose synchronously and/or heterochronously and grew, increasing their sizes in these different organs. Microscopic examinations revealed that all of the cysts were composed of squamous epithelium, dense lymphoid tissue with germinal centers, and a fibrous capsule. These findings corresponded to those of BCCs or LECs. It is notable that the histopathological features were nearly the same in the individual organs. A review of the literature disclosed no previous such reported cases. The etiology is unknown. However, based upon the similar histopathological features of all the excised specimens, common immune and/or hematopoietic disorders may have contributed to their occurrence and development in association with putative genetic abnormalities.